Laser activation method towards printable Cu/Ag-based current collectors for microsupercapacitor-embedded electrical circuits - Baek, Beomjung; Jo, Yejin; Bae, Sang Hyeok; Choe, Yumin; Lee, Hyun Jung; Yang, Chan Hyeon; Cho, Yong Jun; Cho, Min Kyung; Park, Jung Hwan; Jeong, Sunho (Elsevier BV, 2026)
A printable metallic current collector is essential for realizing monolithically integrated microsupercapacitors (MSCs), but its practical implementation has been limited by a critical trade-off between cost-effectiveness, electrical conductivity, and electrochemical stability. Here, we report a photothermally tailorable laser activation strategy that enables digitally printable, highly conductive and electrochemically robust Cu-based current collectors. By synergistically combining the low reflectivity of Cu flakes and the strong localized surface plasmon resonance of Ag nanoparticles, we designed a highly efficient photothermal annealing method that induces the photochemical removal of electrically insulating Cu oxide and promotes the surface-conformal formation of a graphitized carbon passivation layer. The resulting Cu/Ag current collector delivered an electrical conductivity of 1,340,000 S m−1, overwhelmingly surpassing all of Ag/Ag, Cu/Cu and Ni/Ni counterparts. The Cu/Ag-MSC exhibited superior performance compared to other counterparts, including even the vacuum-deposited Cr/Au, in terms of capacitance, energy density, power density, and cost-effectiveness. We also confirmed that series/parallel-connected Cu/Ag-MSC arrays drastically outperform those employing the Ni current collector that has been recognized to date as a representative cost-effective candidate. Most importantly, the digitally patternable Cu/Ag current collectors enabled on-demand, mask-free fabrication of MSC-embedded electrical circuits with 50.5 cm-long interconnections, without any degradation in electrochemical performance.